Laparoscopic distal pancreatectomy with regional lymphadenectomy through retroperitoneal-first laparoscopic approach (Retlap) for locally advanced pancreatic body cancer. (December 2020) - Kiguchi, Gozo; Sugioka, Atsushi; Kato, Yutaro; Uyama, Ichiro
Abstract: Background: Laparoscopic distal pancreatectomy (LDP) is widely performed [1, 2 ]. However, LDP with regional lymphadenectomy for locally advanced pancreatic cancer (LAPC) is technically demanding [3 ]. We previously reported a new strategy named "retroperitoneal-first laparoscopic approach (Retlap)" for distal pancreatectomy with en bloc celiac axis resection [4 ]. In this study, Retlap is applied during LDP with regional lymphadenectomy (see Fig. 1 ). Methods: This video demonstrates the case of a 70-year-old woman with a 100 × 40-mm LAPC. Preoperative computed tomography revealed a large tumor near the root of the celiac axis and acute pancreatitis in the pancreatic head. An ample dorsal margin should be secured and regional lymphadenectomy performed because of the large tumor. In Retlap, the celiac axis was exposed using the retroperitoneal approach from the dorsal side of the pancreatic body, and then the left adrenal grand and left celiac ganglion were removed. Without interfering with the tumor, the root of the splenic artery was identified, facilitating easy performance of lymphadenectomy around the celiac axis and superior mesenteric artery in Retlap. After dividing the splenic artery, the procedure was converted to laparoscopic approach and resection was completed. Results: The operative time and estimated blood loss were 487 min and 45 mL, respectively. Pathological examination confirmed a negative surgical margin, and R0 resection was achieved with uneventful postoperative course. Conclusion: Retlap was technically feasible and useful for achieving adequate and secure surgical margin and regional lymphadenectomy. Retlap can help secure the operative field of view in difficult cases of LAPC. Highlights: Retlap was applied for laparoscopic distal pancreatectomy with regional lymphadenectomy. The patient has a 100 × 40-mm pancreatic body cancer with preoperative pancreatitis. Retlap was useful to obtain an adequate dorsal margin even in patients with large tumor. This video demonstrates the detailed concept and procedure of Retlap.